THE SOVIET SMALL-CIRCULATION SAMIZDAT: ANALYSIS AND RESULTS - SĖDAITYTĖ, EDITA (Knygotyra, 2012)
The object of this work is samizdat publications in Lithuania during the Soviet occupation. The aim of this study was to identify what types of research have published by now and how to develop the further analysis of samizdat. The study has shown, that Lithuanian researchers analyze samizdat in three different aspects: as part of dissident movement, as part of the Lithuanian press history, and as a unique phenomenon. The terms defining samizdat are not used systematically, but the most frequent terms are samizdat, underground press, illegal press, and dissident press. There are diferent opinions about the emergence of samizdat. Some historians associate the beginning of samizdat with “Lietuvos Katalikų Bažnyčios kronika”, some say that samizdat is part of illegal press started in the nineteenth century, and others that samizdat emerged in the 1950s. Different authors suggest different classification models of the underground press. The basis of all classifications is the division into religious and secular press, but the terminology is different in every research. Also, there is no consensus in historiography, how the secular and the religious forms of samizdat are connected with each other. Some historians analyze only the religious underground press and ignore the other types of samizdat. Some say that other types of underground press have already been studied and nothing new can be said. Some scientists look for the ways to show connections between different types of samizdat. Only E. Jaseliūnas and V. Stonienė tried to analyze samizdat in the aspects of book science: to examine the authorship of articles, printing specifics and release date issues. There are only a few works about the secular periodical samizdat, and there is absolutely no analysis of the non-periodical underground press. The further scientific analysis requires a deeper study of sources; it is necessary to examine the recently detected samizdat press and search for more of it, because not all samizdat press has been found and registered.